Graphic environment for evaluation of binary mixtures - KALOYAN YANKOV (International Journal of Pharma and Bio Sciences, 2016)
Binary mixtures of drugs allow the elaboration of a medicament with new properties, such as the therapeutic effect can be reduced or enhanced. The last quality is very valuable because finding the proper ratio of ingredients can give a drug that possesses the necessary properties, at the same time have reduced side effects such as toxicity, the quantity of the applied dose, high price, etc. Finding such a ratio between the components, in which the mixture will satisfy pre-defined requirements is a serious problem. The task can be solved using multi-objective optimization algorithms or computer aided interactive procedure. In this article, the possibilities of interactive optimization of binary mixtures are described. The parameters characterizing the binary mixtures: individual dose reduction ratios, dose reduction index, combination index, dose ratio, total amount of components and price of mixtures are discussed. New parameters for evaluation - the reciprocal of individual dose reduction ratios and the dose reduction index are introduced. The analytic dependencies of parameters as a function of each of the components are worked out. Graphical interface for visualizing functions and their evaluation during interactive modification of the mixture ingredients is built. The approach is implemented in the computer program KORELIA-Ident.